Mapping Climate Change Education: Reflections from an Education Design-Based Research Project from Northern British Columbia, Canada - Banack, Hartley; Litz, David; Ho Younghusband, Christine; Lautensach, Alexander; Crandall, Joanie; Thielmann, Glen (The Canadian Journal of Action Research, 2025)
Climate change education poses significant challenges for K-12 teachers in northern British Columbia (B.C.) due to the complexity of the challenges of climate change and limited support for integration into teaching practice. In response to the 2022 Accord on Education for a Sustainable Future, the Climate Education in Teacher Education (CETE) project was initiated at the University of Northern British Columbia (UNBC). CETE aims to address an urgent need to respond to the changing climate of northern B.C., where warming is occurring 2-3 times faster than in southern B.C., by equipping teachers with practical and tailored approaches and supports. Using the methodology of Education Design-Based Research, CETE employs the conjecture mapping method to develop educational interventions and refine trajectories to be responsive to local realities. Over three years (2022-2025), CETE has engaged in strategic collaborations with climate change education experts, resulting in the generation of seven high level conjectures that guide research and action. This paper examines patterns around roles of community cooperation and iterative design, through action research aimed towards empowering northern B.C. teachers and researchers to respond climate change education demands by considering agency, creative pedagogy, educational leadership, and climate change adaptation, in hopeful and intentional ways.